A Love-Based Curriculum from a Hadith Perspective: A Conceptual Analysis of the Integration of Values of Compassion and Ahlak in Islamic Religious Education - Asep Hikmatullah; Moh. Nasir; Ramdani Nopandri; Namiyah Fitriani; Ibnu Imam Al Ayyubi (-, 2026)
This study aims to analyze a love-based curriculum from the perspective of hadith and the integration of compassion and moral values (akhlak) in Islamic religious education. This research employs a qualitative approach of the library research type and the thematic (maudhu'i) approach to hadith studies. The results show that compassion is a fundamental aspect of Islamic teachings. The Prophet's hadiths not only serve as a normative source of Islamic teachings but also possess significant pedagogical dimensions in building an educational paradigm. The values contained in the hadiths, such as rahmah (mercy/compassion), empathy, gentleness, social care, and morals (akhlak), constitute the primary foundation for designing a humanistic curriculum. The love-based curriculum model from the hadith perspective consists of three main components. First, the source of values, namely the hadiths of Prophet Muhammad (peace be upon him) which contain the principles of compassion and morals as the theological basis of education. Second, the core values, which include rahmah, empathy, gentleness, care, and morals (akhlak), serving as the foundation in education. Third, curriculum integration, i.e., the application of these values into the main components of the Islamic religious education curriculum: objectives, content or materials, methods, and learning evaluation.